The lady and the officer [large type] - Ellis, Mary, 1951- (Ellis, Mary, 1951- Civil War heroines series, 2014)
When Madeline Howard saves the life of Elliott Haywood, a colonel in the Confederate Home Guard, he becomes determined to win her favor, but Madeline's political sympathies are with the North, and her heart belongs to a Northern soldier.